Safety at the swimming pool - Raatma, Lucia (Mankato, Minn. : Bridgestone Books, 1999)
Discusses the safety aspects of swimming in a public pool, including such topics as having a buddy, listening to the lifeguards, shallow and deep water, diving boards, and emergencies.
Includes bibliographical references (p. 24) and index.
Keywords: Swimming -- Safety measures -- Juvenile literature; Swimming for children -- Safety measures -- Juvenile literature; Swimming -- Safety measures; Safety